The Effect of Lemon Juice (Citrus limon L.) Treated with Melatonin on the Health Status and Treatment of K14HPV16 Mice - Fátima Badiche-El Hilali; Beatriz Medeiros-Fonseca; Jéssica Silva; Ana C. Silvestre-Ferreira; Maria João Pires; Rui M. Gil da Costa; Francisco Peixoto; Paula A. Oliveira; Daniel Valero (MDPI AG, 2024)
Lemon is a fruit rich in antioxidant properties and has several health benefits, namely the reduction of skin edema and anticarcinogenic properties, which are due to its high content of bioactive compounds. Melatonin can improve and preserve the properties of lemon for longer and also has health benefits. The aim of this study was to evaluate the effects of oral administration of lemon juice after melatonin treatment on murinometric parameters of wild-type (WT) mice and transgenic mice carrying human papillomavirus (HPV). Two trials were performed for oral administration of the lemon extract compound: in drinking water and in diet. First of all, lemons were treated by immersion with melatonin at 10 mM. Then, lemons were squeezed, and the juice obtained was freeze-dried and stored to be subsequently added to drinking water or diet, according to the assay. Thus, mice were divided into eight groups in the drink assay (each with n = 5): group 1 (G1, WT, control), group 2 (G2, WT, 1 mL lemon), group 3 (G3, WT, 1.5 mL lemon), group 4 (G4, WT, 2 mL lemon), group 5 (G5, HPV16, control), group 6 (G6, HPV16, 1 mL lemon) group 7 (G6, HPV16, 1.5 mL lemon) and group 8 (G6, HPV16, 2 mL lemon). The diet assay was divided into four groups: group 1 (G1, WT, control), group 2 (G2, WT, 4 mL lemon), group 3 (G3, HPV16, control) and group 4 (G4, HPV16, 4 mL lemon). In the drink assay, the highest concentration of melatonin (308 ng/100 mL) was for groups 4 and 8, while in the food assay, there was only one concentration of melatonin (9.96 ng/g) for groups 2 and 4. Both trials lasted 30 days. During this time, body weight, food and water were recorded. Afterward, they were sacrificed, and samples were collected for different analyses. At the concentrations used, the lemon juice with melatonin had no adverse effects on the animals' health and showed a positive outcome in modifying weight gain and enhancing antioxidant activity in mice. Moreover, a reduction in the incidence of histological lesions was observed in treated animals. Further research is needed to better understand the effects of lemon extract on health and treatment outcomes in this animal model.